Real estate investment as a panacea for economic instability in Nigeria: evidence from northeastern states of Nigeria - Kasim, Rozilah; Bello, Muhammad Umar; Ahmad Aliyu, Aliyu; Martin, David (Path of Science, 2017)
Real estate investment is an emerging business in many countries of the world. Real estate investment was thoroughly investigated to come up with solution faced by the transaction of land and building. Real estate investment is strictly related to the housing price. It has been pointed out by many researchers that the housing price is affected by many factors, such as interest rate, land supply, government policies and inflation rate. The research highlighted most important aspects of the outcomes. An increase in international real estate capital flows could foster increasing demand for stronger institutions across a global real estate market. The method adopted in this research was quantitative through which 100 questionnaires were developed and distributed within the study area (Bauchi, Gombe, Adamawa and Yobe States). The simple percentage was used to analyzed the data collected. The research is exploratory in nature; hence, a non-probability purposive sampling technique was used for the study. The finding of the research vindicated that real estate investment has a significant role in sharpening the economy of the region, and also the findings revealed that real estate investment opportunity is huge. And again for suggested that housing provision cannot be realized only by private individual excerpts through government intervention. The study concludes that real estate investment, if explore it will create a reliable return to the investment owners, the benefits that can be derived from real estate investment, has been revealed by this study. The study also highlighted that private developers are key important for real estate investment in Nigeria. The conclusion drawn by this research shows that real estate investment has a capacity of transforming economic hardship in the country.